Implementation of Saturday Market to Increase Interest and Knowledge of Entrepreneurship Towards Golden Indonesia 2045 - Mukhlisin, Mukhlisin; Rusdarti, Rusdarti; Khafid, Muhammad; Hadromi, Hadromi (Proceedings of International Conference on Science, Education, and Technology, 2024)
The Saturday market program is an entrepreneurship project of Kurikulum merdeka co-curricular to strengthen the character profile of Pancasila students. This research aims to analyze the influence of the program in increasing entrepreneurial interest and knowledge toward the golden Indonesia 2045. This research used mixed-method research. Data were collected through questionnaires, interviews, and documentation. The research participants were 112 seventh-grade students at Al-Fahd Islamic Junior High School Jakabaring, South Sumatra. The results show that there were two main benefits (1) Increased self-interest of students related to entrepreneurship; (2) Increased knowledge of students related to entrepreneurship. These two benefits are the way to increase the number of entrepreneurs in Indonesia towards the golden Indonesia of 2045.